Joint direction finding and array calibration method for MIMO radar with unknown gain phase errors. Issue 14 (1st November 2016) - Li, Jianfeng; Ding, Ji; Jiang, Defu
Abstract : A novel method for joint direction finding and array calibration in multiple‐input multiple‐output (MIMO) radar with unknown array gain phase errors is proposed. The transmit array and receive array are innovatively arranged along different axes, which are orthogonal to each other. After the trilinear decomposition, the influenced transmit direction matrix and receive direction matrix are combined to estimate the angles, and the gain phase errors can be calculated subsequently. The proposed algorithm is suitable for both uniform linear array (ULA) and non‐ULA, and it can achieve favourable angle and gain phase errors estimation without any auxiliary sensors and any information of the gain phase errors. Furthermore, it has better estimation performance and lower complexity than the eigenstructure method. Simulation results verify the usefulness of the approach.